The Role of Merdeka Belajar Curriculum in Improving Quality Culture at FKIP Kutaikartanegara University Tenggarong, East Kalimantan - Saidi, Sui'd; Istiarsono, Zen; Sudrajat, Didi (International Journal of Education and Digital Learning (IJEDL), 2024)
This study investigates the role of the Merdeka Belajar Curriculum in enhancing the quality culture at FKIP Universitas Kutaikartanegara Tenggarong, East Kalimantan. The primary objective is to assess how the implementation of this curriculum impacts teaching practices, student engagement, and overall educational quality. A qualitative research method was employed, involving interviews with faculty members, administrative staff, and students, coupled with observations and document analysis. Data were analyzed to identify supporting and inhibiting factors influencing the development of a quality culture under the new curriculum framework. The findings reveal that the Merdeka Belajar Curriculum has significantly improved the quality culture at FKIP Universitas Kutaikartanegara. The curriculum's flexibility has facilitated the adoption of diverse and innovative teaching methods, leading to enhanced teaching effectiveness and greater student engagement. Faculty members reported increased adaptability in their instructional approaches, while students experienced more interactive and relevant learning experiences. Additionally, the curriculum has fostered greater student autonomy and responsibility, contributing to improved academic performance and motivation. However, challenges such as administrative adjustments and resistance to change among some staff have been identified as barriers. Addressing these issues is crucial for sustaining and further enhancing the positive impact of the Merdeka Belajar Curriculum on the institution's quality culture.